CHLOROPHYLL AND CAROTENOID CONTENT IN WOLFBERRY (LYCIUM BARBARUM L.) LEAVES - Ion Roșca; Aliona Glijin; Nina Ciorchină; Maria Tabără; Alina Cutcovschi Muștuc; Tudor Ralea; Nina Zdioruc (Agricultura, 2022)
The aim of the study included the spectrophotometric quantification of chlorophyll and carotenoid pigments and the estimation of the ratios of the respective pigments in the species Lycium barbarum L. from the spontaneous flora and in four cultivars of this species ('Licurici', 'New big', 'Amber Sweet' and 'Ning Xia N1'), obtained by tissue culture in the Laboratory of Embryology and Biotechnology of the "Alexandru Ciubotaru" National Botanical Garden (Institute).